Human myoma tissue-based extracellular matrix models for testing the effects of irradiation on the HPV positive cells - Tuominen H; Al-Samadi A; Salo T; Rautava J (BMC, 2022)
Background: This study was designed to investigate the invasion of human papillomavirus (HPV) positive human cervical carcinoma cell lines in human leiomyoma-based extracellular matrices in vitro,and to test the suitability of the model for studying the irradiation effects on the cancer cell invasion.
Methods: HPV positive cervical carcinoma cell lines SiHa and CaSki, and HPV negative squamous cell carcinoma cell line HSC-3 were used. CaSki cells contain around 600 copies of HPV 16 virus in the genome, whereas SiHa have only 1-2 copies per cell. Cells were analyzed using two different human tumor derived extracellular matrix methods (3D myoma disc model, and Myogel Transwell invasion assay). Cultures were irradiated with 4 Gy. Myoma invasion area and the depth of invasion were measured with ImageJ 1.51j8 software. Statistical analyses were performed with SPSS Statistics (IBM SPSS (R) Statistics 25).
Results: All cells invaded through Myogel coated Transwell membranes and within myoma discs. In myoma discs, a difference in the invasion depth (p = 0.0001) but not in invasion area (p = 0.310) between the HPV positive cell lines was seen, since SiHa (less HPV) invaded slightly better than CaSki (more HPV). HSC-3 cells (HPV negative) invaded deepest (p = 0.048) than either of the HPV positive cell line cells. No difference was detected in the invasion area (p = 0.892) between HPV positive and HPV negative cells. The ionized radiation significantly reduced the invasion depth of HSC-3 (p = 0.008), SiHa (p = 0.0001) and CaSki (p = 0.005). No significant effect on the invasion area was detected in any of the cell lines. However, a significant difference was observed between SiHa and CaSki in the reduction of the invasion depth after radiation (p = 0.013) as the reduction was greater with SiHa than CaSki.
Conclusions: Both solid and gelatinous human leiomyoma-based extracellular matrix models were suitable platforms to study the invasion of HPV positive cervical carcinoma cells in vitro. SiHa cells with less HPV copy number cells invaded slightly better and were slightly more sensitive to irradiation than CaSki cells with high HPV copy number. However, there was no drastic differences between the invasion properties of these carcinoma cells.